Cost-Effectiveness of Posaconazole vs. First-Generation Triazoles for the Prevention of Invasive Fungal Infections Among High-Risk Patients With Hematological Malignancies in China - Shi, Changcheng; Ye, Jian; Xie, Yaping; Dong, Rong; Jin, Weizhong; Wang, Linling; Fang, Yingying; Shan, Qiyuan; Lin, Nengming (Frontiers in Public Health, 2022)
Background: Posaconazole is confirmed to be more effective for preventing invasive fungal infections (IFIs) than first-generation triazoles (fluconazole and itraconazole), but its economic value has not been comprehensively evaluated in China. This study compared the cost-effectiveness of these two antifungal prophylaxis regimens in hematological-malignancy patients at high risk for IFIs from the Chinese healthcare perspective. Methods: A hybrid decision tree and Markov model were built using published data to estimate the total costs and quality-adjusted life-years (QALYs) of antifungal prophylaxis with posaconazole oral suspension and first-generation triazoles. Regimens with an incremental cost-effectiveness ratio (ICER) lower than the threshold of willingness to pay (WTP) were considered cost-effective. One-way and probabilistic sensitivity analyses were performed to assess model robustness. The regional imbalance of economic development and the tablet formulation of posaconazole were considered in the scenario analyses. Results: In the base-case analysis, posaconazole oral suspension provided an additional 0.109 QALYs at an incremental cost of 954.7, yielding an ICER of 8,784.4/QALY, below the national WTP threshold of 31,315/QALY. One-way and probabilistic sensitivity analyses showed that the results were robust. Scenario analyses showed that the base-case ICER was consistently below the WTP thresholds of all 31 Chinese provinces, with the likelihood of posaconazole being cost-effectiveness ranging from 78.1% to 99.0%. When the posaconazole oral suspension was replaced by the tablet formulation, the ICER increased to 29,214.1/QALY, still below the national WTP threshold and WTP thresholds of 12 provinces. Conclusions: Posaconazole oral suspension is a highly cost-effective regimen for preventing IFI in high-risk hematological-malignancy patients from the Chinese healthcare perspective. Posaconazole tablets may also be considered in some high-income regions of China.